A multi-functional porous cobalt catalyst for the selective hydrogenative ring-opening and rearrangement of furfural to cyclopentanol. Issue 9 (1st April 2022) - Li, Xing-Long; Zhu, Rui
Abstract : Multi-functional Co-400 catalyst via the simple reduction of commercially available Co3 O4 for the conversion of furfural to cyclopentanol was developed. Abstract : Developing an economic catalyst to upgrade furfural to cyclopentanol is highly significant for fine chemical synthesis and biomass utilization. In this manuscript, an efficient and economical multi-functional porous Co-400 catalyst was developed. This catalyst obtained porosity, magnetism, Lewis acidity and hydrogenation activity via simple reduction of purchased Co3 O4 . Various factors were investigated in detail, and 87% yield of CPL could be obtained when Co-400 was used as the catalyst. The active sites of the catalyst were identified according to XRD, IR, XPS, SEM and Raman analysis. Moreover, the keys to the high activity and chemoselectivity of the Co-400 catalyst were mainly attributed to highly dispersed Co 0 species and amorphous porous Co3 O4 species, which were precisely controlled by the reduction temperature. The catalyst can be easily separated by magnetism. Furthermore, a possible reaction mechanism was proposed based on a series of controlled experiments and catalyst characterizations.